Effects of oxygen-related damage on dwell-fatigue crack propagation in a P/M Ni-based superalloy: From 2D to 3D assessment. (June 2017) - Jiang, R.; Bull, D.J.; Proprentner, D.; Shollock, B.; Reed, P.A.S.
Highlights: Oxidation at crack tip on side surface and at low ΔK level enhances crack propagation. Oxides are rarely observed at the crack tip in the bulk material at high ΔK level. Dynamic embrittlement may contribute to enhanced crack propagation at high ΔK level. X-ray CT is able to capture 3D crack morphology in Ni-based superalloy. 3D crack features are considered when evaluating oxygen-enhanced crack propagation. Abstract: Effects of oxygen-related damage ( i.e. oxidation and dynamic embrittlement) on fatigue crack propagation behavior in an advanced disc alloy have been assessed in air and vacuum under dwell-fatigue conditions at 725 °C. The enhanced fatigue crack propagation is closely related to oxygen-related damage at/ahead of the crack tip, which is determined by the testing environment, the dwell period and the crack propagation rate itself based on two dimensional (2D) observation of the crack tip in an optical microscope and scanning electron microscope. X-ray computed tomography has also been employed to examine the differences between three dimension (3D) crack morphology in air and vacuum conditions, and the crack features have been quantified in terms of crack opening displacements, secondary cracks and uncracked bridging ligaments. The results show that the fatigue crack propagation rate is related to the amount of secondary cracks, and the crack length increment in a loading cycle is related to the breaking/cracking of the uncracked bridging ligaments within the discontinuous cracking zone ahead of the crack tip as oxygen-related damage preferentially occurs in these highly deformed regions. By combination of 3D X-ray computed tomography and traditional 2D observation, a deeper understanding is provided of the mechanisms of oxygen-enhanced fatigue crack propagation behavior.